On the right to peaceful assembly as a guarantee of freedom of expression: some reflections on Ukrainian law and practice - Yarmol, Liliya (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article discusses theoretical issues of a general character concerning the freedom of expression and right to peaceful assembly. The functional relations between both freedoms, in particular, the protective function of the freedom of peaceful assemblies with regard to the collective exercise of freedom of expression, are examined. Furthermore, the author evaluates Ukrainian regulations and judicial practice with regard to the discussed freedoms in light of international standards. The article culminates with some proposals for amendments to Ukrainian law aimed at introducing mechanisms that would ensure more effective protection of the discussed freedoms. It is especially problematic that there are no statutory provisions that would specify limitation clauses of the freedom of assembly as enshrined in Article 39 para. 2 of the Constitution of Ukraine, and that would regulate procedural aspects related to the enjoyment of that freedom, in particular the issue of prior notification of the intent to hold an assembly. The absence of the said provisions created a lacuna, which prompted some courts to apply laws dating back to the times of the former USSR. This resulted in the unconstitutional endorsement of the requirement to obtain a prior permit to hold a peaceful assembly imposed by administrative authorities. Furthermore, the absence of specific provisions on freedom of assembly resulted in many arbitrary administrative decisions establishing a ban on exercising civic freedoms that constitute the pillars of a democratic society. On the other hand, the examination of statistical data concerning the courts decisions issued in recent years shows that there is an increase in the efficiency of judicial protection of constitutional freedoms, which should reflect itself in the future practice of public administration.

W artykule zostały przedstawione ogólne zagadnienia teoretyczne dotyczące wolności wypowiedzi oraz wolności zgromadzeń. W szczególności analizie poddano związki funkcjonalne zachodzące pomiędzy obiema wolnościami, zwłaszcza funkcję gwarancyjną pełnioną przez wolność zgromadzeń w odniesieniu do kolektywnego korzystania z prawa do wolności wypowiedzi. Ponadto autorka dokonała oceny zgodności ze standardami międzynarodowych treści ukraińskich regulacji prawnych oraz praktyki orzeczniczej w zakresie ochrony omawianych wolności. Artykuł zawiera także postulaty de lege ferenda dotyczące wprowadzenia do ustawodawstwa Ukrainy mechanizmów zapewniających skuteczniejszą ochronę omawianych wolności. Zdaniem autorki szczególnym problemem jest brak przepisów ustawowych, które konkretyzowałyby klauzule limitacyjne wolności zgromadzeń zawarte w art. 39 ust. 2 Konstytucji Ukrainy oraz normowałyby aspekty proceduralne korzystania z tej wolności, zwłaszcza kwestię uprzedniego zawiadomienia o zamiarze przeprowadzenia pokojowego zgromadzenia. Brak wskazanych przepisów spowodował lukę w prawie, co skłaniało niektóre sądy do stosowania prawa pochodzącego z czasów ZSRR. Prowadziło to do niezgodnego z obowiązującą konstytucją sankcjonowania wymogu uzyskiwania pozwolenia na przeprowadzenie zgromadzenia stosowanego przez organy administracji. Ponadto brak szczegółowych regulacji wolności zgromadzeń stał się przyczyną wielu arbitralnych decyzji administracyjnych ustanawiających zakaz korzystania ze swobód obywatelskich, stanowiących fundamenty demokratycznego społeczeństwa, w tym wolności zgromadzeń. Z drugiej strony z analizy statystycznej orzeczeń sądów administracyjnych z ostatnich lat wynika, iż nastąpił wzrost skuteczności sądowej ochrony swobód obywatelskich, co w przyszłości powinno przełożyć się na praktykę stosowania prawa przez organy administracji publicznej.
Keywords: freedom of expression; right to peaceful assembly; human rights guarantees; jurisprudence of the Supreme Court of Ukraine; wolność wypowiedzi; wolność pokojowych zgromadzeń; gwarancje praw człowieka; orzecznictwo Sądu Najwyższego Ukrainy